2023
DOI: 10.1177/00207640231166629
|View full text |Cite
|
Sign up to set email alerts
|

Network of burnout, depression, anxiety, and dropout intention in medical undergraduates

Abstract: Background: Burnout, depression, and anxiety are highly prevalent among medical students, which often leads to their attrition. We aim to assess the inter-relationships of depression, burnout, and anxiety symptoms with dropout intention among Chinese medical undergraduates using the network analysis. Method: A total of 3,648 Chinese medical undergraduates were recruited through snowball sampling. Learning burnout scale, 9-item Patient Health Questionnaire (PHQ-9), and General Anxiety Disorder Scale (GAD-7) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 47 publications
0
8
0
1
Order By: Relevance
“…En el análisis bibliométrico, se observó que algunas palabras clave mantuvieron una relevancia constante a lo largo del tiempo, mientras que otras ganaron importancia. Por ejemplo, la palabra "ansiedad" ha sido utilizada en diversas investigaciones (Brumariu, et al, 2022;Jystad et al, 2021;Peng et al, 2023;Syvertsen et al, 2020).…”
Section: Conclusionesunclassified
“…En el análisis bibliométrico, se observó que algunas palabras clave mantuvieron una relevancia constante a lo largo del tiempo, mientras que otras ganaron importancia. Por ejemplo, la palabra "ansiedad" ha sido utilizada en diversas investigaciones (Brumariu, et al, 2022;Jystad et al, 2021;Peng et al, 2023;Syvertsen et al, 2020).…”
Section: Conclusionesunclassified
“…Higher scores indicated more severe symptoms. PHQ9 and GAD7 were highly validated and widely used measurement tools in the Chinese population (18). Following a previous study (17), a cutoff point of 10 for PHQ-9 and GAD-7 was used to detect the presence of depressive and anxiety symptoms.…”
Section: Mental Distressmentioning
confidence: 99%
“…To date, emerging studies have documented the network structure of mental distress (mainly depression and anxiety) in different populations such as the general population (16), adolescents (17), college students (18), and healthcare workers (19,20) during the COVID-19 pandemic. However, to our knowledge, only two studies assessed the network of mental distress in COVID-19 patients (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…Academic burnout refers to a negative psychological and behavioral state in which students have low interest, lack of motivation, and tiredness in studying ( Lian et al, 2014 ). A recent survey conducted among 3,648 samples found that academic burnout is prevalent among Chinese college students, with a prevalence rate of 38% ( Peng et al, 2023 ). Academic burnout not only affects students’ academic performance ( Gao, 2014 ), but also has negative impacts on their mental health ( Shi et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Academic burnout not only affects students’ academic performance ( Gao, 2014 ), but also has negative impacts on their mental health ( Shi et al, 2023 ). College students experiencing academic burnout are more prone to suffer from depression, anxiety, and internet addiction ( Cheng and Lin, 2023 ; Nizam et al, 2023 ; Peng et al, 2023 ). Considering the total large number of Chinese college students in 2022, which has reached 46.55 million (data from the website of the Ministry of Education of the People’s Republic of China 1 ), as well as the increasing cost of higher education, it is crucial to identify the factors influencing academic burnout among Chinese college students and explore intervention strategies to reduce it for the sake of students’ psychological well-being.…”
Section: Introductionmentioning
confidence: 99%